Antibiotic resistance—consequences for animal health, welfare, and food production. (May 2014) - Bengtsson, Björn; Greko, Christina
Abstract Most of the literature on the consequences of emergence and spread of bacteria resistant to antibiotics among animals relate to the potential impact on public health. But antibiotics are used to treat sick animals, and resistance in animal pathogens may lead to therapy failure. This has received little scientific attention, and therefore, in this article, we discuss examples that illustrate the possible impact of resistance on animal health and consequences thereof. For all animals, there may be a negative effect on health and welfare when diseases cannot be treated. Other consequences will vary depending on why and how different animal species are kept. Animals kept as companions or for sports often receive advanced care, and antibiotic resistance can lead to negative social and economic consequences for the owners. Further, spread of hospital-acquired infections can have an economic impact on the affected premises. As to animals kept for food production, antibiotics are not needed to promote growth, but, if infectious diseases cannot be treated when they occur, this can have a negative effect on the productivity and economy of affected businesses. Antibiotic resistance in animal bacteria can also have positive consequences by creating incentives for adoption of alternative regimes for treatment and prevention. It is probable that new antibiotic classes placed on the market in the future will not reach veterinary medicine, which further emphasizes the need to preserve the efficacy of currently available antibiotics through antibiotic stewardship. A cornerstone in this work is prevention, as healthy animals do not need antibiotics.